Odd Hoftun's Perspective on Hydropower Development in Nepal - Bista, Shiva (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
Not available DOI: 10.3126/hn.v5i0.2490 Hydro Nepal Vol. 5, July 2009 Page:50